2006
DOI: 10.1038/sj.onc.1209635
|View full text |Cite
|
Sign up to set email alerts
|

Spreds, inhibitors of the Ras/ERK signal transduction, are dysregulated in human hepatocellular carcinoma and linked to the malignant phenotype of tumors

Abstract: Aberrant activation of the Ras/Raf-1/extracellular-regulated kinase (ERK) pathway has been shown to be involved in the progression of human hepatocellular carcinoma (HCC). However, the mechanism of dysregulation of ERK activation is poorly understood. Recently, we identified Sprouty-related protein with Ena/vasodilator-stimulated phosphoprotein homology-1 domain (Spred) as a physiological inhibitor of the Ras/Raf-1/ ERK pathway. In this study, we found that the expression levels of Spred-1 and -2 in human HCC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
131
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 152 publications
(137 citation statements)
references
References 36 publications
6
131
0
Order By: Relevance
“…Other studies also found that phosphorylated ERK level is higher in HCC tissues and ERK activation is associated with aggressive tumor behavior (Schmitz et al, 2008). In addition, negative regulator proteins of MAPK/ERK pathway such as Sprouty and DUSP1 are down-regulated in HCC tumors (Calvisi et al, 2008) (Yoshida et al, 2006). Sustained www.intechopen.com activation of ERK signaling can also occur due to point mutations in the RAS gene, which leads to constitutive CRAF activation (Downward, 2003;Whittaker et al, 2010).…”
Section: Mapk Pathwaymentioning
confidence: 99%
“…Other studies also found that phosphorylated ERK level is higher in HCC tissues and ERK activation is associated with aggressive tumor behavior (Schmitz et al, 2008). In addition, negative regulator proteins of MAPK/ERK pathway such as Sprouty and DUSP1 are down-regulated in HCC tumors (Calvisi et al, 2008) (Yoshida et al, 2006). Sustained www.intechopen.com activation of ERK signaling can also occur due to point mutations in the RAS gene, which leads to constitutive CRAF activation (Downward, 2003;Whittaker et al, 2010).…”
Section: Mapk Pathwaymentioning
confidence: 99%
“…Furthermore, after immunohistochemical evaluation of tissue samples, there was an approximately sevenfold increase in MEK1/2 phosphorylation in HCC tissues, compared with that in adjacent benign liver tissues (Huynh et al, 2003). The MAPK negative regulatory proteins RKIP (phosphatidylethanolamine binding protein 1) and the Sprouty (Spry)/Spred proteins are downregulated in HCC tumors, and this decrease is postulated to have a role in the excessive activation of the MAPK pathway observed in HCC (Schuierer et al, 2006;Yoshida et al, 2006). Other studies using in vivo HCC models and human HCC tissue specimens have shown an increase in the expression and activity of signaling intermediates, such as phosphorylated ERK, compared with surrounding liver tissue (McKillop et al, 1997;Ito et al, 1998;Feng et al, 2001).…”
Section: Hcc Signaling Review S Whittaker Et Almentioning
confidence: 99%
“…The product of the hepatitis B virus X gene (HBx protein), the core protein of hepatitis C virus (19 -21), down-regulation of Ras inhibitors such as RASSF1A and NORE1A (22), Sprouty 2 (23), and Sproutyrelated protein with Ena/vasodilator-stimulated phosphoprotein homology 1 and 2 (24), and up-regulation of interleukin-6 (25) and insulin-like growth factor-II (26,27) have all been shown to activate the Ras/Raf/MEK/ERK pathway in HCC. Activated Ras turns on Raf kinases that phosphorylate and activate MEK1/2, which in turn activates ERK1/2.…”
Section: Introductionmentioning
confidence: 99%